Measuring the product quality of Malaysian herbal industry:a pilot study - Rozita , Mokhtar; Mazita, Mokhtar; Muhammad Aiman , Zulkifli (2017)
This pilot study applies a Theory of Quality Management (TQM) Underlying the Deming Management Method, by Anderson et al. (1994) in the field of herbal industries in Malaysia. As an effort to develop a flexible data collection tool, a questionnaire was developed to measure the outcomes of herbal product quality. In 2016, 100 questionnaires were distributed to the respondents which are the employees of 10 herbs firms in Malaysia, registered under the National Pharmaceutical Control Bureau (NPCB). All data are usable. The questionnaire is adopted and adapted from Anderson et al. (1995) and are organized in 6 parts. The research variables are Visionary Leadership, Internal and External Cooperation, Learning Organization, Process Management, Continuous Improvement, Employee Fulfilment and Customer Satisfaction (a reflection of Product Quality). The instrument’s content validity were examined by a panel of experts while the construct validity were examined by factor analysis, which to reduce and simplify irrelevant data and remove appropriate items. The finding identified the well-performed question items that should be retained, and the poorly performed items that should be dropped or need further study. Reliability analysis and normality test were also run using SPSS software. The result indicated the data is reliable and the data exhibit reasonable normality. This pilot study shall be followed with a full research in future. The full research is recommended to apply a TQM Underlying the Deming Management Method by Anderson et al. (1994) in investigating the factors that influence herbal product quality in Malaysia.